Transformations of the Military Profession and Professionalism in Scandinavia - Roelsgaard Obling, Anne (Scandinavian Military Studies, 2021)
What characterises the development and social transformation of the military profession in Scandinavia? Has the broadening of tasks, function and scope of the military profession lead to changes in the values, outlook and behaviour of groups of the armed forces? And what kind of changes are the cultural and structural interpenetration of civilian and military spheres, including hybrid forms of professionalism, generating and what are the significance and implications of such changes?;Transformations of the Military Profession and Professionalism in Scandinavia brings together a number of expert scholars within Military Studies and related fields to provide timely and updated answers to these highly important questions - answers with potential implications far beyond the Scandinavian case.